Al-Quran dalam Perspektif Tafsir Muhammad Abduh - Gaffar, Abd. (Media Akademika, 2008)
Holy Quran in exegesis perspective of Muhammad Abduh is a significant Islamic asset in the development of Quranic exegesis science, because his exegesis thoughts are still exist for Islamic development until now. It seems that its influence never stop to discuss in various scientific forums up to now. Hence, his exegesis ideas invite many interpretation experts and researchers to highlight it as an object of study which need to be developed. His exegesis to Quran is admitted having orientation to cultural social and scientific theory. He tried to interpret the cultural social events and scientific experiments with the verses of Quran then adjust to the situation at that time, so that impress that Quran didnt contradicted with periods development.